2016
DOI: 10.1259/dmfr.20160075
|View full text |Cite
|
Sign up to set email alerts
|

Image quality assessment of clinically-applied CBCT protocols using a QAT phantom

Abstract: The image quality of the CS 9300 CBCT varied with variability in exposure protocols and different voxel sizes. The negative association between greater spatial resolution (smaller voxel size) and the MTF shows that the slanted edge method is not ideal for MTF evaluation of CBCT and is therefore not recommended for using it for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…According to the studies of the 25 phantoms, 7 phantoms possess features for evaluating 4 or more image quality parameters, 10,23,[30][31][32]34,37 while 11 phantoms can be used to test merely 1 parameter. Only two phantoms permit the evaluation of the six image quality parameters as stated by the European Commission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the studies of the 25 phantoms, 7 phantoms possess features for evaluating 4 or more image quality parameters, 10,23,[30][31][32]34,37 while 11 phantoms can be used to test merely 1 parameter. Only two phantoms permit the evaluation of the six image quality parameters as stated by the European Commission.…”
Section: Resultsmentioning
confidence: 99%
“…In two of the phantoms, 17,35 this parameter is evaluated from a pattern bar while in nine phantoms, it is evaluated using the modulation transfer function from wires or spheres with a high atomic number. 10,14,20,21,23,31,32,34,37 In one of the phantoms, 29 both methods can be used.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the main advantages of CBCT, namely the higher spatial resolution and lower patient dose compared to medical computed tomography CBCT modality has an increasing interest in the dental practice [27], nevertheless inaccurate image quality can lead to misdiagnosis and unnecessary radiation dose for the patient. Thus it is worthwhile to assess the image quality of the CBCT device and other radiographic imaging system quantitatively to ensure the diagnostic accuracy of the chosen modality [28]. Spatial resolution, which is related to the ability of distinguishing two adjacent structures on a radiograph, is one of the parameters, which can be measured objectively allowing us to estimate the imaging performance of an X-ray based medical system [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Brüllmann et al [29] found in their review, that there is a large variance between the values of observer based visual assessment and the quantitative MTF determination. In addition, numerous studies focusing on MTF measurements as a possible way for quantitatively evaluate the X-ray based imaging devices using cone-beam geometry [28,30,33,[35][36][37]. The image quality and consequently spatial resolution is influenced by several other factors such as focal spot size, overall geometry, tube voltage, tube current, exposure time, rotation arc, the size of field of view (FOV) and the reconstruction parameters as well as the image noise and the movement of the object [7,29,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used the modulation transfer function (MTF) parameter to measure spatial resolution, and Nakahara et al recommended using MTF values instead of line pair values for routine quality assurance programs 3. In previous studies, the MTF has been measured in different conditions, with varying devices, phantoms, and exposure conditions 35678910. This variation makes it difficult to compare MTF values across studies, and it is impossible to determine reference values for optimization or quality assurance of CBCT images.…”
Section: Introductionmentioning
confidence: 99%